A shape stability model for 3D printable biopolymer-bound soil composite. (28th February 2022) - Biggerstaff, Adrian; Lepech, Michael; Fuller, Gerald; Loftus, David
Highlights: An elastic–plastic model is developed to predict the post-printing height of a material layer for 3D printing. Slump testing data is used to validate the elastic–plastic model. The slump test is evaluated as a method to predict the yield stress and wet elastic modulus of Biopolymer-bound Soil Composite (BSC). A BSC design guide is presented for determining shape stability of a printed layer. Abstract: When 3D printed layers are laid down, the printed material must retain its shape. Material flow or deformation can result in an undesirable reduction in layer height and potential structural instability. Therefore, designers must predict and account for deformation of printed material in structural design. This paper proposes an elastic–plastic model for determining the post-printing height of a 3D printed Biopolymer-bound Soil Composite (BSC) layer. The model is validated using the slump data for five BSC mixtures. Slump test experiments are also used to develop relationships between slump, soil volume fraction, and material density. We find that the elastic–plastic model, along with a slump test, can be used to accurately predict the final, post-printed height of a Biopolymer-bound Soil Composite (BSC) layer.